De Valois' Turkish venture Richard Glasstone on de Valois' achievements in Turkey - Glasstone, Richard (Dance Books Ltd., Alton,Hampshire (UK), 1999)
PALABRAS CLAVE: Ninette de Valois, Turkish State Ballet Company.